Comparison of dose volume histograms and international commission of radiation units and measurement point doses to bladder and rectum in carcinoma cervix patients treated with intracavitary brachytherapy in department of radiotherapy - Priya, Munagapati Vishnu; Benjamin, Gandi Joseph; Sagar, Rasapalli Vineeth (ScienceRise: Medical Science, 2022)
International commission of radiation units and measurement point doses to the bladder and rectum in carcinoma cervix patients treated with intracavitary brachytherapy in the department of radiotherapy. The aim: to evaluate two-dimensional point-based dose planning and three-dimensional computed tomography-based dose-volume parameters for high-dose-rate intracavitary brachytherapy of cervical cancer. Materials and methods: prospective study done between the years June 2018 to April 2020, a total of 50 prospectively registered women of non-metastatic carcinoma cervix treated with definitive concurrent chemo-radiotherapy followed by HDR intracavitary brachytherapy who met inclusion criteria were accrued in the study. All women in the study were treated with 50 Gy EBRT then assessment was done for response and adequacy for comfortable insertion of application. Brachytherapy procedure was performed under sedation in the lithotomy position. Results: Median age of the entire group was 54.5 years, majority of them were in their 5th (34 %) or 4th (28 %) decade. Pathologically, all were squamous cell carcinoma. Most common subtype was large cell non keratinizing type (64 %). Major bulk of the study is contributed by stage IIA, IIB, IIIB. All patients were treated with external beam radiotherapy of 50Gy in 25 fractions with 2Gy per fraction followed by high dose rate brachytherapy of 7 Gy per fraction for 3 fractions, one week apart to a total intracavitary brachytherapy dose of 21Gy. Conclusion: Results from the study suggests that rectum ICRU reference points can be surrogate markers for D2cc, but not for bladder and hence reporting should preferably be done in volumetric method rather than reference point doses